Altered Expressions of NF1 and NF1-Related microRNAs as Biomarkers in the Diagnosis of Undifferentiated Pleomorphic Sarcoma - Zhang, Peng; Huang, Lingling; Ma, Pengwei; Niu, Xiaoying (Frontiers in Genetics, 2022)
Objective: Undifferentiated pleomorphic sarcoma (UPS) is a highly malignant, aggressive, and pleomorphic subtype of soft tissue sarcoma in adults. However, UPS is difficult to be diagnosed due to the lack of specific morphological and immunophenotypic features. Here, we aimed to identify new biomarkers for the diagnosis of UPS. Methods: The mRNA and protein expression of neurofibromin 1 (NF1) in 68 pairs of UPS and adjacent normal tissues were detected by qRT-PCR and immunohistochemistry, and the correlation between the NF1 protein expression and clinicopathological characteristics was analyzed. Then, differentially expressed microRNAs (DE miRNAs) were identified between the UPS tumor tissue and matched adjacent normal tissue using Hisep sequencing, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG). The DE miRNAs of the regulating NF1 gene were also identified using the TargetScan and miRanda databases and validated by qRT-PCR. Results: Compared with the adjacent normal tissue, both mRNA and protein expressions of NF1 in the UPS tumor tissue were significantly decreased, and the positive rate of NF1 protein was associated with the tumor size, metastasis, and recurrence. A total of 125 known DE miRNAs were identified from the screened miRNAs based on | log2(Fold Change) ≥5 and p-value < 0.05 (A total of 82 upregulated and 43 downregulated DE miRNAs in the UPS tissue). Target genes regulated by the DE miRNAs were enriched in pathways of metabolisms, RNA degradation, PI3K-Akt, and Rap1 pathway. In total, 11 miRNAs which were predicted to regulate the NF1 gene were screened. After verification, the relative expressions of hsa-miR-199a-3p and hsa-miR-34a-5p were increased and decreased in the UPS tumor tissue compared with those in the adjacent normal tissue, respectively. Conclusion: NF1 and NF1-related microRNAs including hsa-miR-199a-3p and hsa-miR-34a-5p may be novel biomarkers in the diagnosis of undifferentiated pleomorphic sarcoma (UPS).